The Gap Liability of Substitute Notary on the Authentic Deed which is Made based on the Terms of Notary Position - Danang Sanjaya; Bambang Tri Bawono; Widayati Widayati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to identify and analyze an authentic deed made by a substitute notary has the same power as perfect evidence as made by a notary official, to know and analyze the concept of a substitute notary so that the authentic deed product meets the requirements as perfect evidence like a notary official, and to find out and analyze examples of substitute notarial deeds. The research approach method used in this thesis is a normative juridical law research method. This research specification uses descriptive analysis. The type of data used in this research is primary data which includes the 1945 Constitution; Act No. 2 of 2014; Civil Code; and secondary data containing books, journals and other supporting documents. Collecting research data with techniques literature, laws, government regulations, and regulations under the law, journals, scholarly opinions, and legal cases. The data analysis method used in analyzing the data is a qualitative analysis of the interactive model. The results show that the authentic deed made by the substitute notary has a procedure regarding the provisions, the conditions that must be carried out since the notary official takes leave and the Minister of Law and Human Rights gives a letter of appointment of a substitute notary.